Multiobjective Optimization Method for the Diversion Scheme of Lean Concrete Overtopped Cofferdam under Multiconstraint Conditions. (7th February 2023) - Dong, Zhengyu; Shi, Kebin
Abstract : In this paper, a multiobjective optimization method considering both time limit and cost of lean cemented overtopped cofferdam diversion scheme as objectives is proposed. In the multiobjective optimization method, the main constraint condition is the reliability of the construction period, which also considers the design specification, dam site rainfall, construction capacity, and other constraint conditions. Pareto solutions with the diameter of the diversion tunnel and the height of cofferdam as parameters are obtained using perturbation weight method. Finally, the optimal scheme was obtained according to the importance of the critical node project period and its free time difference. The case study showed that the cost is low, the construction period is reasonable, and the results are consistent with the expert decision system in this model. The Monte Carlo method was used to simulate the construction of lean cemented cofferdam. The study shows that the construction speed of lean cemented cofferdam is slow under frequent rainfall condition. The lower limit of construction speed of key projects greatly affects the scheme. Increasing construction equipment redundancy is an important way to increase construction speed. The free float time difference of cofferdam construction is the key point of scheme decision.